Negotiating the Third Space: Islamic Performing Arts and Cultural Diplomacy Between Muslim Minorities and Royal Patronage in Bali - Sariada, I Ketut; Gunadi Putra, I Gede; Rahiminejat, Rahim (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
In Bali, Islamic performing arts have long bridged relations between Muslim minority communities and the puri royal courts, shaped by trade, intermarriage, and mutual coexistence. This study examines Rodat as a medium of social interaction and identity negotiation in Kepaon, Denpasar, and Puri Agung Pemecutan, with comparisons from other regions in Bali. Using a qualitative ethnographic approach that combines observation, interviews, and document analysis, the research traces the historical, symbolic, and political dimensions of these practices. The findings show that Rodat and other Islamic performances serve dual functions: preserving Muslim identity while legitimizing palace authority, creating a third space that enables coexistence without forced assimilation. This space functions as a mechanism of interfaith diplomacy, reinforced through rituals, mutual recognition, and cultural patronage. In doing so, this study advances theoretical understanding by demonstrating how Bhabha’s ‘third space’ can be institutionalized through traditional patronage, enabling coexistence without assimilation.